Penerapan Budidaya Ikan Lele Intensif Sistem Aquaponik sebagai Upaya Peningkatan Produksi Ikan pada Kelompok Pembudidaya Ikan di Kabupaten Banyuwangi - Prayogo; Fasya, Arif Habib; Maulana, Muhammad Hilmy; Prayogo, Andhika Mufid (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The fisheries potential of Banyuwangi Regency is substantial due to its abundant natural resources. The Fish Farmers Group (Pokdakan) Sumber Bening serves as a productive partner located in Rejopuro Hamlet, Kampunganyar Village, Glagah District, Banyuwangi Regency, an area situated within a watershed (DAS) that supports aquaculture activities. This Community Service Program (Pengmas) aims to empower the Sumber Bening fish farmers group as a productive partner; however, they face challenges related to low production output. Initial identification revealed two main problems: limited human resource capacity in intensive catfish cultivation and weak technical management. The interventions implemented included the establishment of an aquaponic cultivation demonstration plot, technical training sessions, as well as continuous mentoring and evaluation. The results showed a significant improvement in skills and competencies—from 8% before training to 75% after training—along with an increase in motivation to develop from 10% to 80%. The final capacity improvement reached 100% in both indicators, indicating successful technology transfer and adoption of intensive aquaculture practices. The partner group successfully implemented Standard Operating Procedures (SOPs) for cultivation, conducted daily record-keeping, and achieved improved feed efficiency, reduced mortality rates, and produced additional outputs in the form of organic vegetables. The growth performance indicated a Feeding Rate (FR) of 1:1 and a Survival Rate (SR) of 99%. This program resulted in the development of a model fish farming group that is adaptive and has strong potential for replication in other regions.